ANALISIS EFISIENSI PRODUKSI PETANI PADI PESERTA OPERASI PANGAN RIAU MAKMUR (OPRM) DI KABUPATEN KAMPAR - Lena Marjelita; Fajar Restuhadi; Jumatri Yusri Yusri (Indonesian Journal of Agricultural Economics, 2015)
Riau Province is the province with abundant natural resources,such as petroleum, oil palm, coconut, and cacao and other plantation commodities.Nevertheless, the contrary condition happens in the aspect of food commodities. Riau Province still relies on its needs of food from the neighbor provinces, namely West Sumatra Province, North Sumatra, Jambi and importing from overseas.One of the main problem that happens in Riau Province is the lack of food production or the deficiency between production and needs of consumption which tend to increase and if the number of food deficiency is not reduced, the food insecurity is about to worry to happen in the future. In line with the national food security policy and in order to reduce the dependence of rice supply from other regions in 2013 therefore in 2009 The Government of Riau Province launched a program named Operasi Pangan Riau Makmur (OPRM). The aims of the research are: (1)to figure out the profile of farmers as the participants of OPRM Program in Kampar Regency (2) to analyze the dominant factors affecting the lowland rice farming activities in Kampar Regency (3) to analyze factors affecting paddy production and technical efficiency level and the alocative aspect of lowland rice farming in Kampar Regency.The method of analysis used in the research were qualitative (descriptive) analysis to answer the first aim, Cob-douglas production function analysis to answer the second aim and frontier production function and multiple function of border cost with DEAP approach to answer the third aim. The result showed that the land area, ureum fertilizer, SP36 fertilizer, organic fertilizer, labor, land suitability, experience in farming activity and education affected the production significantly. In general the farmers as participants and the non-participantsof OPRM program have been efficient technically, but they were not efficient in alocative and economic aspect.